Prophylactic Antibiotics in Elective Laparoscopic Cholecystectomy is it Necessary? - Sharma, Anup; Shah, Arun (Journal of Nepalgunj Medical College, 2018)
Background: Elective laparoscopic cholecystectomy (LC) has a low risk for Surgical Site Infection (SSI). In spite many surgeons still use prophylactic antibiotics. The aim of this study was to find out the need of prophylactic antibiotics in elective LC.Method: This study was carried out from 2017 June to 2018 August in the Department of Surgery Nepalgunj Medical College and Teaching Hospital Kohalpur (NGMC). Patients were placed into two groups. Group A received a single dose of prophylactic antibiotic and group B patients did not receive any prophylactic antibiotic. In both groups the SSI were recorded and compared.Results: Overall SSI was 5(3.33%) among 150. In group A 2 (2.66%) patients had SSI and in group B 3 (4%) had SSI. Using or not using prophylactic antibiotics did not correlate with SSI (p= .154).Conclusions: Prophylactic antibiotic is not recommended in elective LC. Prophylactic antibiotic does not reduce the rate of SSI.